PEMBERIAN AIR KELAPA DAN KOMPOS SEKAM PADI TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobrom cacao L.) - Ninda Putri; Armaini Armaini; Sri Yoseva Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Cocoa is a plantation crop that had important role for the national economy. Increasedthe cocoa production and development was determined by the availability of high quality seedling. High quality seedling were obtained by  the high quality seed and and good breeding process by giving coconut water as a nature ZPT and using soil medium by adding rice husk compost.This research was carried out at Screen House and Plant Ecaphysiology Laboratory, Faculty of Agriculture, University of Riau. This research was conducted experimentally using Completely Randomized Design (CDR) factorial consist of two factors. Fist factor was the consentrasion of coconut water consist of four level doses (25%, 50%,75% and 100%). Second factor was the rice husk compost dose consist of three leve doses (0 g dose per 5 kg soil,150 g dose per 5 kg soil and 300 g dose per 5 kg soil). The observed parameter include seed height, rod diamater, number of leaves, leaf area, root volume, root crown ratio, and dry seedling weight. Research finding showed that the combination 75% coconut water and 150g rice husk compost increased rod diameter and dry weight. By giving 100% coconut water concentrate  increased  plant height, leaf area and dry weight. By giving 150% rice husk compost increased plant height, rod diameter, root       volume, and dry            weight.Keywords: Cocoa, Coconut Water, Rice Husk Compost